Andean ancestral knowledge and technologies: resistance practices in the Ayllu of Guaymallén (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This paper gives an account of the extension project developed in the province of Mendoza, Argentina, in connection with an indigenous organization called “Ayllu de Guaymallén. Comunidad Indígena Intercultural” located on the urban periphery, a reception area for Bolivian migrants since the end of the 20th century. In a context of poverty and precariousness of the neighborhoods and popular settlements, the Bolivian indigenous women, workers of Ayllu de Guaymallén and the team of extensionists integrated by teachers and fellows of the UNCuyo and researchers of the INCIHUSA – CCT Mendoza, generated a collaborative diagnosis and participatory which came from the demand to coordinate and manage experiences in the Ayllu. This demand took shape in the project Dialogue of ancestral knowledge and technologies as practices of resistance benefited, in the 14th call of the Mauricio López Extension Projects (hereinafter ML) and developed during 2022. Here we try to critically reflect on: the experiences, strategies, activities and actors involved in the organization of the tasks; bonds and relationships, knowledge and learning, emotions and care; obstacles and skills, impacts and repercussions.
Keywords: Reproductive work; precarious work; Unpaid work; Care work; Feminization of poverty